Review of the modern educational editions on latin language for nonspecialized faculties (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article analyzes textbooks, manuals and dictionaries developed by Latin lecturers of National University of Life and Environmental Sciences of Ukraine. The review of latest scientific and methodological learning aids on discipline «Latin language» for nonspecialized faculties is conditioned by need to improve the professionally oriented data base of Latin terminology.
Keywords: Latin; nonspecialized faculties; modern manuals; electronic dictionary